"Dere dame, to-day demay yow neuer": Gendering Fear in the Emotional Community of Sir Gawain and the Green Knight. (2nd July 2016) - Yeo, Jayme M.
Abstract : Using recent work in the history of emotions, this article argues that Sir Gawain and the Green Knight constructs an "emotional community" at Camelot by resolving a tension in late medieval conceptions of courage and fear. Historians suggest that fear played a productive role in a knight's martial identity despite apparent injunctions to unmitigated courage in romance literature and conduct books. This fact gives rise to incompatible emotional imperatives in Sir Gawain . Specifically, the Green Knight's terrifying entrance at Camelot discloses the knights' fear and frames Gawain's journey to Hautdesert as an attempt to reclaim bravery for the Round Table. The poem ultimately accomplishes this feat through a series of emotional negotiations that reconstruct the Christmas events to reveal female characters as the retrospective objects and subjects of the male fear of death. The result is not to eliminate fear from Camelot's chivalric identity, but rather to preserve it within a space of internal difference. By relegating courage and fear to gendered narrative space, the poem is ultimately able to authorize the simultaneous existence of both emotions, thereby unifying the opposing emotional energies circulating within Camelot.